You are what you eat: is suboptimal larval diet linked to the slow recovery of the Newfoundland capelin stock? - Hannah M. Murphy; Samantha Trueman; Gabrielle Perugini; Janine O’Reilly; Dominique Robert (Reviews in Fish Biology and Fisheries, 2025)
Capelin on the Newfoundland and Labrador shelves (Northwest Atlantic Fisheries Organization Divisions 2J3KL) collapsed in 1991 and have experienced only a modest recovery in 30 + years. Year-class strength of Newfoundland capelin is set early in its life history. Using 6 years of larval data (2002, 2006, 2014, 2020–2022), the main objective of this study was to use trophodynamics to identify potential bottom-up drivers of capelin larval survival. The proportion of empty guts generally decreased with ontogeny; however, prey presence was low with only 18.9% of larvae containing at least one prey item in their guts. Larval diet was mainly composed of calanoid copepodites, Pseudocalanus spp., Temora spp., Oithona spp., and phytoplankton. There was a shift in diet with ontogeny, with copepodite stages increasing in importance with ontogeny. Although larval trophodynamics since 2002 differed from those described in the 1980s, with a higher proportion of empty guts and a broader prey spectrum, this comparison is confounded by spatial and temporal limitations of the available dataset. Using general additive models, mean recent 3-day larval otolith growth rate was related to in situ zooplankton prey availability, temperature, salinity, presence/absence of prey, and prey carbon contents. Larval growth was positively associated with copepod nauplii densities in 2 of the 3 years, indicating that a match between larval occurrence and copepod nauplii may be an important driver of larval growth. A match-mismatch between larval occurrence and their preferred prey may be a potential bottom-up mechanism to explain the prolonged Newfoundland capelin stock recovery.

LP-36 Toxicological assessment of isothiazolinone mixtures in zebrafish early life stage: morphological and molecular responses - M.G. Rizzo; A. Iannetta; L. Sulcanese; W. Gentile; C.R. Multisanti; C. Faggio; M. Perugini (Toxicology Letters, 2025)

P08-21 Neurotoxicity of Octylisothiazolinone (OIT): Evidence from Zebrafish Early-Life Stage - L. Sulcanese; A. Iannetta; T. Silvestrini; G. Angelozzi; V. D'Altilia; S. Zugaro; V. Iezzi; E. Benedetti; M. Perugini (Toxicology Letters, 2025)

Decarbonation and clast dissolution timescales for short-term magma‑carbonate interactions in the volcanic feeding system and their influence on eruptive dynamics: Insights from experiments at atmospheric pressure - M. Knuever; R. Sulpizio; D. Mele; A. Pisello; A. Costa; D. Perugini; F. Vetere (Chemical Geology, 2023)

Contamination of basalt through silicic melts: The first chaotic dynamics experiments with Paraná-Etendeka starting materials - Caio M. Vicentini; Cristina P. de Campos; Werner Ertel-Ingrisch; Leila S. Marques; Donald B. Dingwell; Diego Perugini (Chemical Geology, 2023)

Rifting and recharge as triggers of the mixed basalt–rhyolite Halarauður ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)

The San Gregorio Magno lacustrine basin (Campania, southern Italy): improved characterization of the tephrostratigraphic markers based on trace elements and isotopic data - P. Petrosino; I. Arienzo; F. C. Mazzeo; J. Natale; M. Petrelli; A. Milia; D. Perugini; M. D′Antonio (Journal of Quaternary Science, 2019)
Central–southern Italy is one of the most suitable areas in the world for tephrostratigraphic studies, owing to the numerous volcanic sources with explosive activity during the Pleistocene. This work presents a systematic investigation of the chemical (trace elements) and isotopic (Sr and Nd) compositions of the main tephra markers within lacustrine sediments of the San Gregorio Magno Basin (Campania, southern Italy). This study: (i) provides full geochemical (trace elements and isotopes) characterization of eight significant Upper Pleistocene marker layers (X‐6, X‐5, C‐22, MEGT/Y‐7, CI/Y‐5, C‐10, Y‐3, NYT/C2) widely dispersed over the Mediterranean area; (ii) proposes a new tephra marker for Marine Isotope Stage 7, dated to 240 ka; and (iii) refines the correlations of tephra levels belonging to the investigated sequence. This study highlights that in most cases the Nd isotope composition of the glass and Sr isotope composition of the coexisting minerals are more reliable than 87 Sr/ 86 Sr of the glass, and hence is more helpful as a further tool for tephrostratigraphic correlations, as recently proposed in the literature. Moreover, this study is a first step towards the construction of a complete geochemical database for future tephra investigations in the Mediterranean area. Copyright © 2019 John Wiley & Sons, Ltd.

Molecular evolution of an oligomeric biocatalyst functioning in lysine biosynthesis - Tatiana P. Soares da Costa; Belinda M. Abbott; Anthony R. Gendall; Santosh Panjikar; Matthew A. Perugini (Biophysical Reviews, 2018)

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

Experimental constraints on the origin of pahoehoe “cicirara” lavas at Mt. Etna Volcano (Sicily, Italy) - F. Vetere; S. Mollo; P. P. Giacomoni; G. Iezzi; M. Coltorti; C. Ferlito; F. Holtz; D. Perugini; P. Scarlato (Bulletin of Volcanology, 2015)

Monitoring of levels of polycyclic aromatic hydrocarbons in bees caught from beekeeping: remark 1 - M. Amorena; P. Visciano; A. Giacomelli; E. Marinelli; A. G. Sabatini; P. Medrzycki; L. Persano Oddo; F. M. De Pace; P. Belligoli; G. Di Serafino; S. Saccares; G. Formato; et al. (Veterinary Research Communications, 2009)

γ-Irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: I. Effect of Irradiation Doses - R. Dorati; C. Colonna; M. Serra; I. Genta; T. Modena; F. Pavanetto; P. Perugini; B. Conti (AAPS PharmSciTech, 2008)

Influence of landscape morphology and vegetation cover on the sampling of mixed plutonic bodies - D. Perugini; M. Petrelli; G. Poli (Mineralogy and Petrology, 2007)

Time-scales of hybridisation of magmatic enclaves in regular and chaotic flow fields: petrologic and volcanologic implications - M. Petrelli; D. Perugini; G. Poli (Bulletin of Volcanology, 2006)

5-Methyl-Pyrrolidinone Chitosan Films as Carriers for Buccal Administration of Proteins - C Colonna; I Genta; P Perugini; F Pavanetto; T Modena; M Valli; C Muzzarelli; B Conti (AAPS PharmSciTech, 2006)

Improved Detection of Coxiella burnetii in Cows Milk by Immunomagnetic Separation and PCR - F. Capuano; A.G. Perugini; A. Parisi; C.O. Montagna; M. Nilvelli (Veterinary Research Communications, 2004)